2016
DOI: 10.1021/acs.joc.6b02264
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cascade Ring-Closing Metathesis Reactions en Route to an Advanced Intermediate of Taxol

Abstract: Graphical abstractAbstract: A highly functionalized intermediate in the synthesis of Taxol has been synthesized, which features the tricyclic core and the required oxygen substituents at C1, C2, C7, C10 and C13. The key step, a ring-closing dienyne metathesis (RCDEYM) reaction, has been thoroughly optimized to favor the tricyclic product over the undesired bicyclic product resulting from diene metathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In contrast, the RCM of terminal olefins with alkenes that are geminally disubstituted at their terminus (e.g., the prenyl group) in ruthenium benzylidene catalyzed RCM reactions have limited literature precedent. While these examples have shown that such olefin combinations are possible in RCM reactions, the prenyl grouping is most often employed as a matter of synthetic expediency to derive the RCM substrate from readily available terpene building blocks , or in RCM reactions demonstrated directly on monoterpenes . It has also been employed as a rational design feature to direct initiation to another olefin, ,, and it has certainly been noted that the prenyl group functions surprisingly well in selected RCM reactions. ,, However, to the best of our knowledge, there have been no direct kinetic comparison of RCM reactions using acyclic dienes with terminal alkenes versus an acyclic diene where one of the alkenes is now geminally disubstituted at its terminus. Herein, we report on such activities, and experimentally demonstrate that prenyl groups are excellent acceptor olefins in ring-closing metatheses.…”
mentioning
confidence: 99%
“…In contrast, the RCM of terminal olefins with alkenes that are geminally disubstituted at their terminus (e.g., the prenyl group) in ruthenium benzylidene catalyzed RCM reactions have limited literature precedent. While these examples have shown that such olefin combinations are possible in RCM reactions, the prenyl grouping is most often employed as a matter of synthetic expediency to derive the RCM substrate from readily available terpene building blocks , or in RCM reactions demonstrated directly on monoterpenes . It has also been employed as a rational design feature to direct initiation to another olefin, ,, and it has certainly been noted that the prenyl group functions surprisingly well in selected RCM reactions. ,, However, to the best of our knowledge, there have been no direct kinetic comparison of RCM reactions using acyclic dienes with terminal alkenes versus an acyclic diene where one of the alkenes is now geminally disubstituted at its terminus. Herein, we report on such activities, and experimentally demonstrate that prenyl groups are excellent acceptor olefins in ring-closing metatheses.…”
mentioning
confidence: 99%
“…Taxol, one of the most famous anticancer drugs, is among the blockbuster drugs together with its derivatives and to be an attractive synthetic target (Mendoza et al, 2012). Prunet's group (Letort et al, 2016;Ma et al, 2016) investigated the synthesis of taxane and isotaxane derivatives, during which the tricyclic carbocycles were constructed via domino RCM of ene-yne-ene substrates. In the next year, Oterofraga and Granja (2017) reported one-step assembly of a taxanelike skeleton from an ene-yne-yne-ene substrate.…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
“…In their study en route to an advanced intermediate of taxol, 55 the same authors succeeded in assembling the metathesis precursor 65, endowed with a protected hydroxy group at C7. The dienyne RCM turned out to be very challenging, since the presence of a substituent at C7 favored the formation of undesired RCM bicyclic products of type 62 rather than the tricyclic core of taxol.…”
Section: Scheme 17 Preparation Of Taxol-type Carbocyclic Systems Via mentioning
confidence: 99%